2009
DOI: 10.1603/033.046.0419
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Transmission of Vesicular Stomatitis New Jersey Virus From <I>Simulium vittatum</I> to Cattle: Clinical Outcome Is Influenced by Site of Insect Feeding

Abstract: Vesicular stomatitis New Jersey virus (VSNJV) is an insect-transmitted Rhabdovirus causing vesicular disease in domestic livestock including cattle, horses, and pigs. Natural transmission during epidemics remains poorly understood, particularly in cattle, one of the most affected species during outbreaks. This study reports the first successful transmission of VSNJV to cattle by insect bite resulting in clinical disease. When infected black flies (Simulium vittatum Zetterstedt) fed at sites where VS lesions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
(42 reference statements)
1
28
0
Order By: Relevance
“…Biological transmission of VSNJV by black ßies to mice (Mead et al 1999(Mead et al , 2000, domestic swine (Mead et al 2004a), and domestic cattle (Mead et al 2009) has been demonstrated. In addition, colonized biting midges, Culicoides sonorensis Wirth & Jones, are susceptible to VSNJV infection (Nunamaker et al 2000, Drolet et al 2005, and experimentally infected midges have been shown to transmit the virus to guinea pigs ) and cattle .…”
mentioning
confidence: 99%
“…Biological transmission of VSNJV by black ßies to mice (Mead et al 1999(Mead et al , 2000, domestic swine (Mead et al 2004a), and domestic cattle (Mead et al 2009) has been demonstrated. In addition, colonized biting midges, Culicoides sonorensis Wirth & Jones, are susceptible to VSNJV infection (Nunamaker et al 2000, Drolet et al 2005, and experimentally infected midges have been shown to transmit the virus to guinea pigs ) and cattle .…”
mentioning
confidence: 99%
“…To the authors' best knowledge, no literature has reported whether the infection of VSV is uniform in individual cells. Furthermore, the entrance of virus would interfere with cell life cycle progression [22,23,24]. But it is not clear whether the cell life cycle stage itself, upon viral infection, would on the other hand have a selective effect on the ability of adopting viral infection.…”
Section: Infection Heterogeneitymentioning
confidence: 99%
“…In livestock, viraemia was not detected in VSNJV-infected swine (Patterson et al, 1955;Redelman et al, 1989;Comer et al, 1995;Stallknecht et al, 1999Stallknecht et al, , 2001Stallknecht et al, , 2004Mead et al, 2004aMead et al, , 2004b, cattle (Cotton, 1926;Scherer et al, 2007;Mead et al, 2009) or horses (Green, 1993;Howerth et al, 2006). In studies involving wildlife, experimental VSNJV infection of white-tailed deer (Karstad & Hanson, 1957;Comer et al, 1995) and pronghorn antelope (Thorne et al, 1983) did not result in viraemia, which suggests that these wild animals, which are naturally susceptible to VSNJV, are not amplifying hosts.…”
Section: Introductionmentioning
confidence: 99%